A visit from the Goon Squad - Egan, Jennifer (Random House, 2010)
Bennie Salazar, an aging former punk rocker and record executive, and Sasha, the passionate, troubled young woman he employs, confront their pasts in this story about how rebellion ages, influence corrupts, habits turn to addictions, lifelong friendships fluctuate and turn, and how art and music have the power to redeem